Shannin Shamsan COVID-19 Video of Retail Store - Shamsan, Shannin::::::::: (2021)
Shannin Shamsan's video shared on social media of an aisle at a Walgreens store on Grimmer Boulevard in Fremont, California. The video shows the empty shelves in the toilet paper aisle.